Pengaruh Transformasi Digital, Stres Kerja dan Work-Life Balance Terhadap Kinerja Tenaga Kependidikan: Peran Mediasi Keterlibatan Karyawan FIKKES UNIMUS - Ndari Puryanti; Edy Purwanto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background – The rapid integration of digital technology and high-pressure environments in healthcare education necessitates a deeper understanding of how these factors influence staff productivity. This study examines the impact of digital transformation, work-related stress, and work-life balance on employee performance, specifically exploring the mediating role of employee engagement. Aim – This study aims to examine the effects of digital transformation, work stress, and work-life balance on employee performance, with employee engagement as a mediating variable among academic staff at the Faculty of Health Sciences (FIKKES), Universitas Muhammadiyah Semarang. Design / methodology / approach – Using a quantitative approach, data were collected from 58 educational staff members at the Faculty of Health Sciences, UNIMUS, using a total sampling (saturated sample) technique. The structural model was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 Findings – The results indicate that digital transformation, job stress, and work-life balance have a significant direct effect on employee performance. In addition, employee engagement also has a significant direct effect on employee performance. Furthermore, employee engagement mediates the relationship between job stress and employee performance, but does not mediate the relationship between digital transformation and employee performance, nor between work-life balance and employee performance. Conclusion – This study highlights a